PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN TERHADAP TINGKAT KEPUASAN PEGAWAI DI DINAS PERHUBUNGAN KABUPATEN PADANG PARIAMAN - Arivetullatif Arivetullatif; Rini Afrianti; Yanti Murni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The implementation of a computer-based Management Information System is essential for enhancing the efficiency, effectiveness, and performance of human resources in government institutions. This study examines the effect of a management information system on employee satisfaction at the Transportation Office of Padang Pariaman Regency. Using a quantitative approach, data were analyzed through descriptive statistics and multiple linear regression. The population consisted of all employees of the Transportation Office of Padang Pariaman Regency. The independent variables were quality (X₁), perception (X₂), and training (X₃), while employee satisfaction (Y) served as the dependent variable. Results show that quality, perception, and training individually have a significant positive effect on employee satisfaction, with significance values of 0.029, 0.040, and 0.047 respectively. Simultaneously, the three variables significantly influence satisfaction, as indicated by an F-value significance of 0.007, which is below the 0.05 threshold. Collectively, these variables contribute 37.2% to employee satisfaction, while the remaining 62.8% is influenced by other factors outside the research model. The study concludes that optimizing the use of information technology can improve employee performance and service quality. It is recommended that management sustain and enhance organizational performance by maximizing available technological resources to support more effective public service delivery.Keywords : Management Information System, Employee Satisfaction, Service Quality